2015
DOI: 10.1128/mcb.00550-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phosphoinositide 3-OH Kinase p110β in Skeletal Myogenesis

Abstract: Phosphoinositide 3-OH kinase (PI3K) regulates a number of developmental and physiologic processes in skeletal muscle; however, the contributions of individual PI3K p110 catalytic subunits to these processes are not well-defined. To address this question, we investigated the role of the 110-kDa PI3K catalytic subunit ␤ (p110␤) in myogenesis and metabolism. In C2C12 cells, pharmacological inhibition of p110␤ delayed differentiation. We next generated mice with conditional deletion of p110␤ in skeletal muscle (p1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…One component of the IGF pathway, the PI3K component, is essential for skeletal muscle regeneration and is composed of three primary classes (classes I, II, III) that are structurally and functionally distinct. The three class IA PI3K p110 catalytic subunits (α, β, and δ) are expressed in skeletal muscle (Matheny and Adamo, 2010) and of these subunits, p110α and p110β have been shown to positively influence myoblast proliferation and differentiation (Matheny et al., 2012, Matheny et al., 2015). In the early and middle periods following injury, we observed differential enhancer binding and increases in expression of PI3K catalytic subunits p110α ( Pik3ca ), p110β ( Pik3cb ), and p110δ ( Pik3cd ) as well as the PI3K p85α ( Pik3r1 ) regulatory subunit for the injured muscle compared with the contralateral control (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…One component of the IGF pathway, the PI3K component, is essential for skeletal muscle regeneration and is composed of three primary classes (classes I, II, III) that are structurally and functionally distinct. The three class IA PI3K p110 catalytic subunits (α, β, and δ) are expressed in skeletal muscle (Matheny and Adamo, 2010) and of these subunits, p110α and p110β have been shown to positively influence myoblast proliferation and differentiation (Matheny et al., 2012, Matheny et al., 2015). In the early and middle periods following injury, we observed differential enhancer binding and increases in expression of PI3K catalytic subunits p110α ( Pik3ca ), p110β ( Pik3cb ), and p110δ ( Pik3cd ) as well as the PI3K p85α ( Pik3r1 ) regulatory subunit for the injured muscle compared with the contralateral control (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that p110α of PI3K and the PI3K‐mediated signaling pathway exert such functions in MuSCs. Unlike MuSC‐specific deletion of p110α using Pax7‐Cre, which resulted in embryonic lethality (Fig EV2A), that of p110β of PI3K (with a Myf5 ‐Cre line) had no obvious deleterious effects on mouse development and survival, as well as muscle mass and strength in vivo (Matheny et al , ). This is likely due to the fact that p110α is the predominant form of PI3K expressed in QSCs, while p110β is barely detectable in QSCs based on the RNA‐seq data from us and others (Liu et al , ; Ryall et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Generation of bacmid DNA, SF9 insect cell‐mediated virus production, and viral transductions of human myoblasts were performed as described (Matheny et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Real time PCR was performed as previously described (Matheny et al. ), normalizing to HPRT1 gene expression. Primers/probes for real‐time PCR were purchased from Life Technologies: AKT1 (Hs00920503_m1), AKT2 (Hs01086102_m1), AKT3 (Hs00987350_m1), HPRT1 (Hs02800695_m1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation